Sex-Specific Brain Activations during Single-Leg Exercise - Kyoungyoun Park-Braswell; Dustin Grooms; Sandra Shultz; Louisa Raisbeck; Christopher Rhea; Randy Schmitz (International Journal of Sports Physical Therapy)
# Background